I need help please I need help
![I need help please I need help class=](https://us-static.z-dn.net/files/d28/d8627ff106bda8c1dd10e0b24c4b5cbb.png)
Answer:
3(2v - 3)(3v + 2)
Step-by-step explanation:
18v² - 15v - 18 ← factor out 3 from each term
= 3(6v² - 5v - 6) ← factor the quadratic
consider the factors of the product of the coefficient of the v² term and the constant term which sum to give the coefficient of the v- term.
product = 6 × - 6 = - 36 and sum = - 5
the factors are - 9 and + 4
use these factors to split the v- term
6v² - 9v + 4v - 6 ( factor the first/second and third/fourth terms )
= 3v(2v - 3) + 2(2v - 3) ← factor out (2v - 3) from each term
= (2v - 3)(3v + 2)
Then
18v² - 15v - 18 = 3(2v - 3)(3v + 2)